Sedimentological features and depositional conditions of accumulative fans in the lower Serteyka River valley, Western Russia - Piech, Wiktor (Acta Geographica Lodziensia, 2021)
In the Serteyka River valley in western Russia, eight accumulative fans formed at the mouths of ravines were examined geologi-cally and geomorphologically. The test samples were collected from individual geological drillings made with a manual probe, as well as from excavations in the central and distal zones of the fans. Using the Gradistat program, sedimentological indicators were calculated, i.e. mean grain diameter (MZ), standard deviation (sorting – σI), skewness (SkI) and kurtosis (KG),and then particle-size distribution frequency curves, cumulative curves and a Passega C/M diagram were drawn. It has been documented that the grain size of the fan sediments depends on the characteristics of the source material. Analysis of sedimentological indicators (mean grain diameter, sorting, skewness, kurtosis) showed the studied fans deposits to have a large variability of erosion and accumulation conditions. For the deposits of younger fans, the 2nd system of the MZ-versus-σI relationship after Mycielska-Dowgiałło (1995) was distinguished, while for the older, the 2nd, 3rd and 4th systems were recognised. The main process of grain transport within these forms was saltation. The ravines on the eastern slope of the Serteyka valley were most likely created in the periglacial period, while the gullies on the western side of the valley developed in the early modern period.